Age and prognosis in patients with pancreatic cancer: a population-based study. (4th March 2022) - van Dongen, Jelle C.; van der Geest, Lydia G. M.; de Meijer, Vincent E.; van Santvoort, Hjalmar C.; de Vos-Geelen, Judith; Besselink, Marc G.; Groot Koerkamp, Bas; Wilmink, Johanna W.; van Eijck, Casper H. J.; ,
Abstract: Background: The diagnosis of pancreatic ductal adenocarcinoma (PDAC) has an enormous impact on patients, and even more so if they are of younger age. It is unclear how their treatment and outcome compare to older patients. This study compares clinicopathological characteristics and overall survival (OS) of PDAC patients aged <60 years to older PDAC patients. Method: This is a retrospective, population-based cohort study using Netherlands Cancer Registry data of patients diagnosed with PDAC (1 January 2015–31 December 2018). Kaplan–Meier curves and Cox proportional hazards models were used to assess OS. Results: Overall, 10, 298 patients were included, of whom 1551 (15%) were <60 years. Patients <60 years were more often male, had better performance status, less comorbidities and less stage I disease, and more often received anticancer treatment (67 vs. 33%, p < 0.001) than older patients. Patients <60 years underwent resection of the tumour more often (22 vs. 14% p < 0.001), more often received chemotherapy, and had a better median OS (6.9 vs. 3.3 months, p < 0.001) compared to older patients. No differences in median OS were demonstrated between both age groups of patients who underwent resection (19.7 vs. 19.4 months, p = 0.123), received chemotherapy alone (7.8 vs. 8.5 months, p = 0.191), or received no anticancer treatment (1.8 vs. 1.9 months, p = 0.600). Patients <60 years with stage-IV disease receiving chemotherapy had a somewhat better OS (7.5 vs. 6.3 months, p = 0.026). Conclusion: Patients with PDAC <60 years more often underwent resection despite less stage I disease and had superior OS. Stratified for treatment, however, survival was largely similar.